Black infertility and social media engagement: a mixed methodology analysis - Melody Ava Rasouli, M.D., M.B.A; Benette Krizel Sagun, B.S; Kajal Verma, M.D; Cindy M. Duke, M.D., Ph.D (Elsevier, 2022)
Objective: To study social media engagement on Black infertility to better understand why there is lower utilization of in vitro fertilization by Black women despite higher infertility rates. Design: The online analytics module BuzzSumo was used to quantify total engagements with the search term "Black infertility" across the commonly used social media platforms. The 10 article links with the highest engagement were selected from periods in 2020 and 2021. Sources cited in each article were reviewed to identify those that had citations of scientific peer-reviewed journals or national medical organizations. The contents of each article were reviewed for accuracy by comparing the article information against available scientific research and consensus data. Patient(s): Not applicable. Intervention(s): Not applicable. Main Outcome Measure(s): Not applicable. Result(s): After applying the exclusion criteria, nine article links remained in each date range. The highest engagement with the term "Black infertility" was found on Facebook for both 2020 and 2021. Ten percent of content regarding Black infertility in 2020 compared with 50% of content regarding Black infertility in 2021 referenced original studies in peer-reviewed journals. Links with greater social engagement were more likely to have academic sources in 2021 than in 2020 (odds ratio, 1.30). The highest user engagement was found for articles discussing the emotional toll of Black infertility. Conclusion(s): Social media users encounter misleading or inaccurate information regarding Black fertility at similar rates to accurate content. Social media can propagate misinformation, and this study identifies social media as an opportunity to improve education directed toward Black women to increase the utilization of in vitro fertilization services.